Sports isolation and the struggle against apartheid in South African sport: the sports policy of the National Party during the 1980s - Rademeyer, Cobus (Faculty of Humanities, University of the Free State, 2013)
Under the National Party (NP) government sport had been governed by apartheid laws since 1948. Towards the end of the seventies the NP introduced the idea of sports autonomy as their policy going into the 1980s. This was based on the fact that government wanted to withdraw from the development and management of sport in the country. Growing resistance from the opposition, anti-apartheid movements, sports people in South Africa, as well as from the conservative elements within the NP against apartheid in sport, continued to work against government principles. The overwhelming anti-apartheid idea that apartheid in sport was no longer the ultimate goal, but the abolishment of apartheid legislation in general emphasised the pressure on the South African government during the decade under discussion. Various small amendments to the sports policy did not bring much relief, as the struggle against apartheid and apartheid in sport intensified. Government’s frequent reassurance that sports autonomy removed government from the management sphere of sport in the country did not reach base, as various racially inclined laws and acts still ensured that governments had to intervene in sport and the practice thereof from time to time. This culminated in talks between the African National Congress (ANC) and, amongst others, a group of South African sports people, with a view to counteracting the NP’s sports policy and paved the way for more talks towards dismantling apartheid in sport and the normalisation of sporting ties in South Africa and internationally.
Keywords: Sports history; Politics and sport; Apartheid; National Party